Philosophy of Education in Facing The Challenges of The Times: a Humanities Perspective - Sukmayadi, Dodi; Rosalia, Olyvia (Kamara Journal, 2025)
This research explores the implementation of humanities-based philosophy of education in the context of modern educational challenges. The study aims to examine how humanistic values, such as empathy, ethics, critical thinking, and social responsibility, can be integrated into the curriculum and teaching practices to foster holistic student development. Using a qualitative approach with a case study design, the research involves in-depth interviews with educators, students, and experts, as well as document analysis of curricula and educational programs. The findings reveal that institutions applying humanistic principles in their educational framework show significant positive impacts on student character development, including enhanced empathy, social cooperation, and emotional growth. However, challenges such as limited teacher training, lack of resources, and the prevailing focus on academic and technical skills hinder the full integration of these values. The study concludes by recommending a more balanced curriculum that prioritizes humanistic education, alongside policy reforms and teacher development initiatives, to better address the evolving needs of students and society.